Fibroblast growth factor 23 is associated with the presence of coronary artery disease and the number of stenotic vessels. (November 2015) - Hu, Xiang; Ma, Xiaojing; Pan, Xiaoping; Hao, Yaping; Luo, Yuqi; Lu, Zhigang; Bao, Yuqian; Jia, Weiping
Summary Fibroblast growth factor 23 (FGF23) has been reported to be involved in cardiovascular disease. The aim of this study was to investigate the association between FGF23 and the presence of coronary artery disease (CAD), as well as the number of stenotic vessels. A total of 254 eligible participants (167 men and 87 postmenopausal women) were enrolled in this study. Coronary angiography was used for diagnosis of CAD. Serum intact FGF23 levels were determined by a two‐sided sandwich enzyme‐linked immunosorbent assay. The median serum FGF23 levels of the entire study population were 39.9 (33.1–47.5) pg/mL. Serum FGF23 levels were higher in subjects with one‐vessel disease than those without CAD (P < 0.05), which further increased significantly in the subjects with multi‐vessel disease (P < 0.05). Serum FGF23 levels increased with cumulative number of stenotic vessels (P for trend < 0.001). Multiple stepwise regression analysis revealed estimated glomerular filtration rate (standardized β = −0.298; P < 0.001) and body mass index (standardized β = 0.132; P = 0.049) were independent factors correlated with FGF23. Multivariate logistic regression analysis showed that FGF23 was positively and independently associated with the presence of CAD (odds ratio = 1.058, 95% confidence interval = 1.025–1.092; P = 0.001). Additionally, FGF23 was also correlated with multi‐vessel disease significantly (odds ratio = 1.034, 95% confidence interval = 1.007–1.062; P = 0.013). In conclusion, serum FGF23 levels exhibit positive and independent association with the presence of CAD and increase with the cumulative number of stenotic vessels.